Different forms of polarity in neorealism and world-systems theory - Stefan Mandić (Sociološki pregled, 2026)
Modern world relations are characterized by the dissolution of American unipolarity and chaotic international relations. This change in the sphere of geopolitics is no doubt related to the restructuring of the world capitalist system in which the USA is losing the hegemonic status, the central position of the Western countries is becoming questionable, while an increasing number of semi-peripheral regions, due to their economic and political characteristics, are coming closer to the centre. Because of the aforementioned, the modern age may be seen as an era of radical transformation of geopolitical patterns, on account of which the analysis of the basic characteristics of unipolarity, bipolarity and multipolarity is gaining importance. A detailed analysis of neorealism as a theory that has the merit for the development of these concepts is necessary for the most appropriate understanding possible of different forms of polarity. Furthermore, it is theoretically significant to compare neorealistic views of polarity with the world-systems understanding of hegemony in order to adequately study the distribution of power in the international order of the states. The main aim of this paper is to analyze the neorealistic and world-systems viewpoints of polarity in order to create the foundations for exploring today’s dominant form of polarity and to assume which form of polarity will be dominant in the 21st century.
Keywords: polarity; hegemony; neorealism; world-systems theory; international order